Spontaneous haemarthrosis following thrombolytic therapy for myocardial infarction. Issue 775 (May 1990) - Oldroyd, K. G.; Hornung, R. S.; Jones, A. M.; Andrews, N. P.; Dawes, P. T.; Carson, P. H.
Abstract : Two cases of haemarthrosis following thrombolytic therapy for acute myocardial infarction are described. Both patients had active pre-existing inflammatory disease in the affected joints at the time of presentation. This complication of thrombolytic therapy has not been previously reported.